Introduction to Quantum Field Theory - Peskin, Michael E.; Schroeder, Deaniel V. (Kolkata: Levant Books, 1995)
An Introduction to Quantum Field Theory is a textbook intended for the graduate physics course covering relativistic quantum mechanics, quantum electrodynamics, and Feynman diagrams. The authors make these subjects accessible through carefully worked examples illustrating the technical aspects of the subject, and intuitive explanations of what is going on behind the mathematics. After presenting the basics of quantum electrodynamics, the authors discuss the theory of renormalization and its relation to statistical mechanics, and introduce the renormalization group. This discussion sets the stage for a discussion of the physical principles that underlie the fundamental interactions of elementary particle physics and their description by gauge field theories.
Appendix 801-810p.; Bibliography 811-816p.; Index 817-842p.; Reprint 2005.
Keywords: Non-abelian gauge theories; Renormalization; Radiative corrections